Swimming training attenuates the decrease of calcium responsiveness in female infarcted rats - Portes, Leslie Andrews; dos Santos, Alexandra Alberta; Padovani, Carlos Roberto; Oliveira, Natália Cristina de; Serra, Andrey Jorge; Tucci, Paulo J. F. (Frontiers in Physiology, 2022)
Aim: To evaluate the influence of swimming training on calcium responsiveness of the myocardium of rats with different infarction sizes (MI). Method: female Wistar rats, sedentary sham (SS=14), sedentary moderate MI (SMI=8) and sedentary large MI (SLI=10) were compared to trained sham (TS=16), trained moderate MI (TMI=9) and trained large MI (TLI=10). After 4 weeks of MI, the animals swam for 60 minutes/day, 5 days/week, for additional 8 weeks. Papillary muscles of the left ventricle were subjected to different concentrations of extracellular calcium. Inotropism was evaluated through the developed tension (DT), the maximum positive value of the first temporal derivation (+Td/td) and the time to peak tension (TPT). Lusitropism was evaluated by the maximum negative value of the first temporal derivation (-Td/td) and time to 50% relaxation (50%TR). Statistical significance was determined using multivariate analysis of variance and a Hotelling T2 test for the absolute power values of all four extracellular calcium concentrations (p < 0.05). Results: MI depressed inotropism (from 17% to 51%) and lusitropism (from 22% to 54%) of the sedentary rats, but exercise attenuated the losses, especially regarding +dT/dt, TPT, -dT/dt and 50%TR. Exercise attenuated the decrease in myocardial responsiveness, proportionally to the size of the MI. Conclusion: Myocardial calcium responsiveness is favorably affected in animals with moderate and high MI after swimming exercise.